1990
DOI: 10.1172/jci114569
|View full text |Cite
|
Sign up to set email alerts
|

A combination of HLA-DQ beta Asp57-negative and HLA DQ alpha Arg52 confers susceptibility to insulin-dependent diabetes mellitus.

Abstract: Family and population studies indicate that predisposition to insulin-dependent (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
171
4
10

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(204 citation statements)
references
References 21 publications
19
171
4
10
Order By: Relevance
“…However, a large number of healthy relatives have the susceptible genes. Additional genetic information therefore needs to be incorporated into a full model of genetic susceptibility, including characterization of both DQ-A and DQ-B chains [22]. In the present study, HLA identity did not expose relatives to an increased prevalence of autoantibodies and metabolic alterations.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, a large number of healthy relatives have the susceptible genes. Additional genetic information therefore needs to be incorporated into a full model of genetic susceptibility, including characterization of both DQ-A and DQ-B chains [22]. In the present study, HLA identity did not expose relatives to an increased prevalence of autoantibodies and metabolic alterations.…”
Section: Discussionmentioning
confidence: 68%
“…The genetic background may therefore contribute to subclinical Beta-cell dysfunction which may progress in limited cases to clinical diabetes under the influence of immune and environmental factors. Recent molecular findings bring further insights into the genetic susceptibility to Type i diabetes [20][21][22]. However, a large number of healthy relatives have the susceptible genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DLA DQA1 alleles coding for arginine at position 55 (Arg55) in hypervariable region 2 were associated with diabetes (Fig. 4) and might be equivalent to the association with HLA DQA1 Reactivity to canine GAD65 (counts per minute) Arg52 in human diabetes [48]. It is interesting to note that the 'increased-risk' haplotype is common in Samoyed dogs, the breed at greatest risk of developing diabetes.…”
Section: Insulin Deficiency Diabetesmentioning
confidence: 91%
“…However, an elegant study showed that DR4 haplotypes encoding both DRB*0401 (a subtype of DR4) and DQB*0302 were more diabetogenic than DR4 haplotypes encoding only one of these [53] ± thus, DRB1 and DQB1 together could confer susceptibility. The HLA-DQA1 locus also appears to be involved in susceptibility [54,55]. In addition to susceptibility alleles, there are also protective alleles.…”
Section: The Challenges Of Searching For Type I Diabetes Genesmentioning
confidence: 99%